Efektivitas Asap Cair Kulit Buah Randu untuk Mengendalikan Walang Sangit Padi - Iqbal Erdiansyah; Mochammad Fahrur Ramadhani; Damanhuri Damanhuri (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
The liquid smoke from pod shell of randu potentially serves as a botanical pesticide in rice farming and also provides an effective approach in controlling the rice ear bug (Leptocorisa oratorius). Also, the sample produces the maximum dominant compound as phenol (C6H5OH) to regulate these bugs. The research was conducted in Kaliwates district, Jember regency, between May-August 2018, using a non-factorial randomized block design with four treatments, that are control-no treatment, formulation 3, 6, and 9 ml.L-1, in six replications. Consequently, the samples of 3, 6, and 9 ml.L-1 obtained a significant effect, in terms of pest control, attack intensity, empty grain percentage, and dry grain weight per sample. The result showed that the maximum and minimum attack intensity occurred in no treatment samples and formulation 9 ml.L-1 treatments, with an average of 35.31 and 23.13%, respectively. Therefore, the liquid smoke of kapok tree fruit skin peels has been confirmed to effectively control the pest population of rice ear bugs.